Rodenticides - Frederick M. Fishel (EDIS, 2019)
Rodenticides are pesticides designed to kill rodents, primarily mice and rats. However, rodents are not the only species that can be poisoned by rodenticides. Practically any mammal, including humans, can suffer severe effects from unintentional exposure to rodenticides. Rodenticides vary widely in the hazard they present even though they are all designed to kill animals that are physiologically comparable to humans. This new 4-page publication of the UF/IFAS Pesticide Information Office addresses those hazards for rodenticides currently registered in Florida. Written by Frederick M. Fishel. https://edis.ifas.ufl.edu/pi284